Small thermal energy storage units filled with microencapsulated PCMs for building applications - Soares, N. (2016)
Phase change materials (PCMs) can be used in buildings for thermal management and thermal energy storage purposes. This paper experimentally evaluates the heat transfer with conduction dominated solid-liquid phase-change through small thermal energy storage (TES) units with horizontal metallic fins emerging from vertical heated/cooled surfaces. The TES units are made up of a vertical stack of rectangular cavities filled with a paraffin-based microencapsulated PCM - the Micronal® DS 5001 X. The influence of the aspect ratio of the cavities and the influence of the boundary conditions imposed during both charging (melting of the PCM) and discharging (PCM solidification) experiments was analysed. The experimental results are intended to be used in the validation of numerical models. Furthermore, they allow to discuss how the TES units can be used to improve the thermal performance of some existing systems and to design/optimize new TES systems for buildings.